Comparison of Open Vs Closed Reduction of Mandibular Angle Fractures-A Retrospective Institutional based Study - Shreya Kothari1 , Sivakumar M2 , Balaji Ganesh S,3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Fractures of the mandible, particularly in the angle region have been found to have a high incidence.Clinical and radiographic examination along with the basis of displacement help to decide the treatmentmodality for these fractures. Open reduction is generally performed when there is significant deviation andclosed reduction for simple fractures. The most common modality being Open Reduction with InternalFixation(ORIF). The aim of the study is to compare Open Vs closed reduction in patients with fracture in theangle region of the mandible. This retrospective study involved a sample size of 18 patients with mandiblefracture in the angle region. Case records were collected, tabulated and imported to SPSS for statisticalanalysis. Descriptive statistics and chi-square tests were adopted for association of various parameters.Angle fractures were most commonly seen in males(89%) than females. RTA and assault were the mostcommon reason for trauma caused - 39% & 33% respectively. 89% of the treatment done was through openreduction with majority being treated by internal fixation(94%). Angle fracture management depends uponthe severity of the displacement to decide the method of reduction and type of stabilisation. Open reductionwith internal fixation was the most common treatment adopted in this study .